1972
DOI: 10.1126/science.177.4043.65
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate-Nitrite Reaction: Possible Means of Blocking the Formation of Carcinogenic N -Nitroso Compounds

Abstract: The formation of carcinogenic N-nitroso compounds by the chemical reaction between nitrous acid and oxytetracycline, morpholine, piperazine, N-methylaniline, methylurea, and (in some experiments) dimethylamine was blocked by ascorbic acid. The extent of blocking depended on the compound nitrosated and on the experimental conditions. Urea and ammonium sulfamate were less effective as blocking agents. The possibility of in vivo formation of carcinogenic N-nitroso compounds from drugs could be lessened by the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
172
1
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(178 citation statements)
references
References 15 publications
2
172
1
3
Order By: Relevance
“…Accordingly, chlorogenic acid and quercetin (phenolics exhibiting a catechol moiety) were shown to enhance the production of U NO from nitrite at acidic pH [18,19]. On the other hand, ascorbic acid, a compound that exhibits a low redox potential, and actively secreted in the stomach, has also been shown to be an efficient one-electron reductant of nitrite [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, chlorogenic acid and quercetin (phenolics exhibiting a catechol moiety) were shown to enhance the production of U NO from nitrite at acidic pH [18,19]. On the other hand, ascorbic acid, a compound that exhibits a low redox potential, and actively secreted in the stomach, has also been shown to be an efficient one-electron reductant of nitrite [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Green and yellow vegetables are very rich in vitamin C, and has been found to be protective against stomach cancer in a number of experimental and epidemiological studies. Thus, vitamin C may inhibit gastric cancer cell growth, be a possible means of blocking the formation of human carcinogenic N-Nitroso compounds, and may reduce nitrite concentration by 43% (Mirvish et al, 1972;Raineri and Weisburger, 1975;Zhang et al, 2002). A prospective cohort study found a significantly decreased risk of progression to dysplasia or gastric cancer among subjects with high blood ascorbic acid level (OR=0.2, 95% CI=0.1 -0.7) (You et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies suggested that a diet rich in vitamin C was protective, whereas a diet high in salt might increase the risk of stomach cancer (Mirvish et al, 1972;Raineri and Weisburger, 1975;Joossens et al, 1996;Zhang et al, 2002). Sources of vitamin C include fresh foods, such as green and yellow vegetables, fruit and other fresh foods, while salt ingestion is from processed, pickled, preserved, salted foods, and also seasoning (Kagawa, 1991).…”
mentioning
confidence: 99%
“…Ascorbic acid can inhibit nitrosation by acting as a competitive substrate for nitrite (Mirvish et al 1972). …”
mentioning
confidence: 99%